Ceramic Art and Urban Planning for the city of Baghdad (Al-Academy, 2017)
Ceramic art associated with urban growth in the cities, it overlapped with architectural construction, the increasing of population, urban growth, knowledge, and civilization was considered ceramic arts as an important aesthetically architecturally complement in the cities, including those in the squares and architectural institutions in the city of Baghdad .the title (Ceramic Art and Urban Planning in the City of Baghdad) the problem was its wonders : 1- Does ceramic monuments suited their locations in the city of Baghdad with the architectural planning urban of the city.2- Does the recipient interacted with these monuments and the reasons of their existence. Then the aim: knowing the relationship of the ceramic monuments with the urban planning of the city of Baghdad .Then chapter 2, section 1 : architectural urban planning of the cities . The second : architectural design treatments in the contemporary cities. The Third: the visual conversation between ceramic art and architecture. Then the third chapter : the research procedures and samples analysis, then the forth chapter: results and conclusions like :Architects and the planners of contemporary Baghdad did not care about inserting the ceramic samples as a part of urban structure of the city and consultation the artists and specialized persons of ceramic arts movement within the streets and squares design and pedestrians movements.